BIODIVERSITAS DAN PENGELOLAANYA BERDASARKAN ALQUR’AN - Sugiyarto, Sugiyarto (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2011)
Alqur’an is a universal reference for Moslem in their life. There are also many information of biodiversity and their management system so can be used as learning source and reference frame in conservation of biodiversity. The aim of this study is to reveal many information of biodiversity in Alqur’an. The study is done by trace-study of biodiversity information and relevance concepts in Alqur’an, than be analyzed by comparative-qualitative approach, compared with biodiversity concepts in science perspective. There are a lot of biodiversity information in Alqur’an: (1) mentioning of species name in It’s verses, (2) concepts of reproduction and heritance or concepts of diversivication and distinction, and (3) concepts of interrelation and natural equability. In science perspectives, there are biodiversity of gene, species, ecosystem (Biology perspective), and culture (social perspective) as frame of reference in developing of biodiversity management systems. In other, based on Alqur’an there must be added with faith diversity (moral-spiritual perspective). There are difference of moral orders and religion laws and their realization determain human attitude to their environment, especially to the conservation of biodiversity.Key words: Biodiversity, conservation, Alqur’an,